Light-induced chromophore activity and signal transduction in phytochromes observed by (13)C and (15)N magic-angle spinning NMR - Rohmer, Thierry (National Academy of Sciences, 2008)
Both thermally stable states of phytochrome, Pr and Pfr, have been studied by (13)C and (15)N cross-polarization (CP) magic-angle spinning (MAS) NMR using cyanobacterial (Cph1) and plant (phyA) phytochrome sensory modules containing uniformly (13)C- and (15)N-labeled bilin chromophores. Two-dimensional homo- and heteronuclear experiments allowed most of the (13)C chemical shifts to be assigned in both states. Chemical shift differences reflect changes of the electronic structure of the cofactor at the atomic level as well as its interactions with the chromophore-binding pocket. The chromophore in cyanobacterial and plant phytochromes shows very similar features in the respective Pr and Pfr states. The data are interpreted in terms of a strengthened hydrogen bond at the ring D carbonyl. The red shift in the Pfr state is explained by the increasing length of the conjugation network beyond ring C including the entire ring D. Enhanced conjugation within the π-system stabilizes the more tensed chromophore in the Pfr state. Concomitant changes at the ring C propionate carboxylate and the ring D carbonyl are explained by a loss of hydrogen bonding to Cph1-His-290 and transmittance of conformational changes to the ring C propionate via a water network. These and other conformational changes may lead to modified surface interactions, e.g., along the tongue region contacting the bilin chromophore.